2004
DOI: 10.1088/0953-8984/16/39/012
|View full text |Cite
|
Sign up to set email alerts
|

Contributions from surface-modified bulk electronic bands to the reflection anisotropy of Au(110)-(1 × 2)

Abstract: We investigate the temperature dependence of the optical reflectance anisotropy (RA) of the Au( 110)-(1 × 2) surface and find that transitions involving surfacemodified bulk bands contribute to the RA spectrum. The RA peaks observed at room temperature at photon energies of 3.52 and 4.50 eV are assigned to the transitions E F → L u 1 and L 2 → L u 1 , respectively. The assignments are based upon a comparison between temperature-induced shifts in the energy of these RAS peaks and thermovariation optical spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…This view is supported by the observation that in UHV the shape of the spectrum in the range 3.5 eV to 5.0 eV is sensitive to the concentration of monoatomic steps oriented along the [110] as revealed by STM [51] and that Ar ion bombardment and annealing studies [60] give rise to changes in this region of the RA spectrum. The RA spectra obtained from the Au(110) crystal in this work is similar to that obtained in UHV for the Au(110) (1 × 2) surface [47,[56][57][58][59][60] and detailed analysis suggests that the sharp change in intensity that is observed between ~2.3 eV and 2.6 eV arises from a transition at the Γ point in the surface Brillioun zone that involves a surface state located just above the Fermi energy and that the features in the spectrum from 3 eV to 5 eV have their origin in modifications of the bulk band structure induced by changes in surface morphology. The RA spectrum obtained following the UPD deposition of Cu shows a reduction in the intensity of the feature at 2.6 eV and an increase in the intensity of the feature at 3.4 eV.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This view is supported by the observation that in UHV the shape of the spectrum in the range 3.5 eV to 5.0 eV is sensitive to the concentration of monoatomic steps oriented along the [110] as revealed by STM [51] and that Ar ion bombardment and annealing studies [60] give rise to changes in this region of the RA spectrum. The RA spectra obtained from the Au(110) crystal in this work is similar to that obtained in UHV for the Au(110) (1 × 2) surface [47,[56][57][58][59][60] and detailed analysis suggests that the sharp change in intensity that is observed between ~2.3 eV and 2.6 eV arises from a transition at the Γ point in the surface Brillioun zone that involves a surface state located just above the Fermi energy and that the features in the spectrum from 3 eV to 5 eV have their origin in modifications of the bulk band structure induced by changes in surface morphology. The RA spectrum obtained following the UPD deposition of Cu shows a reduction in the intensity of the feature at 2.6 eV and an increase in the intensity of the feature at 3.4 eV.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, RA spectra of flame annealed Au(110) surfaces forming the working electrode of an electrochemical cell have been obtained by two groups [52][53][54][55] and the results compared with those ob-tained from clean Au(110) (1 × 2) surfaces prepared in ultra high vacuum (UHV) [52,[56][57][58][59][60]. These studies demonstrate the potential of RAS as an in-situ probe of electrochemical processes.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, evidence has been found for contributions to the RA response around 3.85 eV and 4.1 eV from bulk band transitions that are anisotropically modified by the (110) surface structure [11]. RAS is known to be sensitive to surface morphology [14][15][16][17] and in a combined RAS and STM study, Bremer et al [14] found that the RA response of Ag(110) in the region 3 to 5 eV is particularly sensitive to surface morphology. Consequently there are several RA profiles of clean Ag(110) that can be observed.…”
Section: Methodsmentioning
confidence: 99%
“…2. RAS spectra of the clean and well ordered (solid line) and ion bombarded (dashed line) (110) surfaces of Cu (top) [9], Au (middle) [10] and Ag (bottom) [11] It is satisfying to note that the superficially diverse RAS spectra of the clean (110) noble metal surfaces can be explained within a consistent framework. We now discuss the physical origins of the RAS spectra of modified noble metal surfaces. )…”
Section: The Clean (110) Surfacesmentioning
confidence: 99%
“…2. It is enlightening to quantify the changes by application of the derivative model: results obtained by Martin et al [9][10][11] are reported in Table 1. The Ar bombarded Au surface is found to be Y-like while those of Cu and Ag are of mixed X and Y character.…”
Section: The Clean (110) Surfacesmentioning
confidence: 99%